ORTHODOX EDUCATION AND RELIGIOUS PRACTICES AT SCHOOLS OF VOLYN VOIVODSHIP (1921 – 1939) - DOBROCHYNSKA, Valentyna; LENARTOVYCH, Oleg (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to analyse religious education as an integral part of the Polish educational model comprehensively, to highlight the problem of maintaining religious tolerance regarding the confessional affiliation of schoolchildren, and to implement the didactic principles of religious education, spiritual and moral education in educational institutions. The research methodology consists of the comprehensive application of general scientific research methods – analysis and synthesis, objectivity, historicism, as well as special historical methods – historical and source studies, historical and comparative, historical and genetic, historical and typological, historical and systemic methods. The scientific novelty consists in the fact that for the first time, based on the analysis of a wide range of sources – two Constitutions of the Second Polish-Lithuanian Commonwealth, government decrees, school legislation, textbooks on the Law of God and the methodology of its teaching, Ukrainian Orthodox periodicals, memoirs, as well as the achievements of the Ukrainian and foreign historiography, the peculiarities of teaching the basics of religious education at school and religious practices have been analysed. The principles of religious pedagogy and the requirements for the personnel of teachers of Law of God have been clarified. Conclusions. Thus, the study of the Orthodox religion at schools of Volyn Voivodeship contributed to the preservation of national identity, an important component of which was confessional memory. The Polish legislation in schools issues ensured the interests of all religious communities. In curricula religion was a mandatory school subject, and teaching the basics of Christian doctrine was entrusted to a person with theological education, mainly parish priests. The Volyn Eparchy and the Theological Seminary in Kremenets united the clergy and laity who worked on curricula, textbooks on Law of God, and teaching methods to ensure the educational process at schools properly. Religious practices played an important role, consolidating the acquired religious knowledge in students and contributing to the formation of moral and spiritual virtues and the observance of piety in everyday life. And yet, despite the declared religious tolerance, Polonization of education was clearly visible in Volyn due to the reduction of Orthodox institutions for training clergy, the increase in Polish and Utraquist schools, which was an integral part of the policy of assimilation of Catholic Poland. Key words: Poland, Volyn Voivodeship, interwar period, school, religion teacher, Orthodox education, religious practices.